آلية تدخل الدولة ودورها في معالجة المشكلة الاقتصادية باستخدام الضوابط الشرعية - دراسة نظرية وصفية ـ - قادر, أ. م. الدكتور فاضل محمود; مارف, م. خليل أحمد (Sulaimani Journal for Humanities, 2023)
This research is entitled: (The Islamic State’s Intervention Mechanism and Its Role in Addressing Some Economic Problems Using Sharia Controls- Descriptive Theoretical Study). The research aims: to highlight the mechanism of the Islamic state’s intervention and its role in solving and treating some economic problems by using legal controls when people need the state’s intervention if the intervention is in the interest of the people. And a statement of the position of the Islamic system in intervening by a mediation between absolute intervention as in the socialist system and non-interference as in the capitalist system, with a statement of the advantages and benefits of state intervention in economic activities to solve some problems by using legitimate controls for the benefit of human beings in society. And a statement of the ruling on state intervention in the Islamic system in economic transactions and activities when needed and in the interest of Islamic law. Intervention is to prevent everything that harms people and leads to the destruction of the nation in all economic activities and phenomena. As for the research methodology: An Economic research in which a descriptive theoretical study was used, in which a statement is made, the extent, how and ruling of the Islamic state's intervention in economic activities when people need and interest when the state intervenes to solve problems. And the most important results were obtained: 1- It is permissible for the Islamic State to intervene when people need to solve some economic problems. 2- The ruler or the Islamic state does not intervene except when people perish through high prices, monopoly, etc., and intervene to address the problem for the benefit of society. 3- The intervention of the Islamic state in the middle between the absolute socialist and capitalist nothingness. 4- The state's intervention is through some legitimate controls to solve the problems concerned. Among the most important recommendations in this research: 1- Taking care of teaching Islamic economics in colleges and institutes to teach the science and system of Islamic economics, which is the most successful system to adhere to. 2- The necessity of the Islamic state’s intervention when people need this intervention to address some problems that can only be addressed by its intervention based on the rule (What is not fulfilled except by it is an obligation). 3- Using legal controls is the best way to treat all kinds of economic problems.
Keywords: key words Mechanism; intervention; economic; community commitment; state; legitimacy; problem; controls; Islamic; activities